Original paper Selected antioxidative enzyme activities in patients with diabetes mellitus type 2 - Błaszczak, Robert; Kędziora, Józef; Ertel, Danuta; Rutkowski, Maciej; Kędziora-Kornatowska, Kornelia; Kornatowski, Tomasz; Rysz, Jacek; Kujawski, Krzysztof; Stachura, Danuta (Archives of Medical Science, 2005)
Background: Chronic hyperglycaemia is considered to be the main reason of diabetes complications. In the prolonged increased glucose concentration the increased generation of reactive oxygen species (ROS) occurs, as well as the disturbances of pro- and antioxidative balance i.e. the oxidative stress. In respect of the great role that the oxidative stress may play in the pathogenesis of type 2 diabetes and its chronic complications the aim of this paper was to evaluate the activity of two selected antioxidative enzymes: superoxide dysmutase (SOD) and catalase (CAT) in erythrocytes of type 2 diabetes patients at different stages of the metabolic balance. Material and methods: 61 type 2 diabetes patients took part in the study. Among them 31 patients met the criteria of the metabolic balance, while 30 patients suffered from metabolically unbalanced diabetes. The control group included 40 healthy people. The activity of SOD-1 in red blood cells was determined using the Misra and Fridovich method. The activity of CAT was determined using the Beers and Sizer method. Results: While comparing the activity of SOD-1 and CAT in each studied group, in the group of type 2 diabetes patients at the stage of the metabolic balance it was found to be the highest Conclusions: Taking into account early development of chronic complications of type 2 diabetes it seems that the differences observed in the antioxidative enzymes activity in type 2 diabetes patients with different degrees of the metabolic balance may be used to monitor the clinical process of the disease.